2013
DOI: 10.1097/ccm.0b013e3182711a1c
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Copied Information by Attendings and Residents in Critical Care Progress Notes*

Abstract: Objective To determine the prevalence and mechanism of copying among ICU physicians using an electronic medical record. Design Retrospective cohort study Setting Medical intensive care unit of an urban, academic medical center Participants 2,068 progress notes of 135 patients generated by 62 resident and 11 attending physicians between August 1 and December 31, 2009. Interventions None Measurements and Main Results 82% of all resident and 74% of all attending notes contained ≥20% copied information (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 21 publications
0
41
1
Order By: Relevance
“…For instance, Edwards et al reviewed a random sample of 239 outpatient primary care, cardiology, and endocrinology notes and found that 10.8% contained copied material (although a definition of copy and paste was not provided) [7]. Conversely, another study of ICU notes (A/P section) found that 82% of resident and 74% of attending notes contained copied elements (defined as ≥20% copied text from another document) [8]. Thielke et al (2006) [9] evaluated how often mental status, podiatry and general physical exams appeared to be copied.…”
Section: Prevalencementioning
confidence: 99%
“…For instance, Edwards et al reviewed a random sample of 239 outpatient primary care, cardiology, and endocrinology notes and found that 10.8% contained copied material (although a definition of copy and paste was not provided) [7]. Conversely, another study of ICU notes (A/P section) found that 82% of resident and 74% of attending notes contained copied elements (defined as ≥20% copied text from another document) [8]. Thielke et al (2006) [9] evaluated how often mental status, podiatry and general physical exams appeared to be copied.…”
Section: Prevalencementioning
confidence: 99%
“…One factor that might be contributing to this is the setting of our research, which only analyzed notes written by residents, compared to other studies, which also included attending physicians. One study done in a critical care setting found 74% copying among attending physicians and 82% among all the physicians in the medical critical care unit [14]. A study done in a Veterans Affairs hospital found the prevalence of copying to be 20% [16].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of EMR has led to an increase in the time spent completing notes, resulting in an increased use of the copy-and-paste function by physicians [13,14]. The last few years have seen an increased interest in the evaluation of EMR.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, 25% of electronic patient charts in a sample from the Veterans Affairs system contained a physical examination generated by copypaste (21). This problem has worsened: a more recent analysis suggests that threequarters of electronic notes written by critical care attendings contain greater than 20% copied information (22). We were unable to find reliable estimates as to the frequency of attesting to or copy-pasting a physical examination not personally performed, but such a practice would have clinical consequences, represent a lost teaching opportunity, and constitute fraudulent billing (23).…”
Section: Physical Diagnosis In the Modern Icumentioning
confidence: 99%